Analisis Faktor-Faktor Kesulitan Menghafal Kosakata Bahasa Arab Siswa Kelas V SD IT Al-Anshor Gedong Tataan - Erna Sulistiawati; Ahmad Hadi Setiawan; Angger Putri Mahardini (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2021)
This research is motivated by the difficulty in memorizing the vocabulary of Arabic for fifth grade students of SD IT Al-Anshor Gedong Tataan. Many students still have difficulty in memorizing vocabulary so that students cannot speak Arabic, especially class V, so the researchers chose to use qualitative descriptive analysis methods. This study aims to describe students' ability to memorize Arabic vocabulary and to analyze the difficulty factor in memorizing Arabic vocabulary for fifth grade students of SD IT Al-Anshor Gedong Tataan. This subject is a fifth grade student at SD IT Al-Anshor, there are 20 students, there are 9 boys and 11 girls. As for the source of data that will be a source of information in this study as many as 10 students with the criteria of 5 girls and 5 boys who still have difficulty memorizing Arabic vocabulary. Data collection techniques used are: observation, interviews, and documentation. The results of this study indicate that the condition of students still has difficulty in reading and writing Arabic and the low interest and motivation of students in learning Arabic as well as family factors regarding awareness and encouragement outside of school, a school environment that does not use Arabic when outside the classroom and inadequate school facilities. It can be concluded that the situation of students in learning Arabic is still having difficulties in reading, writing, and understanding the meaning of each vocabulary, as for the factors of difficulty in memorizing Arabic vocabulary, there are obstacles in learning Arabic, especially in memorizing language vocabulary. Arabic caused by a number of factors, namely internal factors and external factors.‎